Co-authorship networks of Brazilian postgraduate programs in Accounting - Welter, Larissa Marx; Souza, Ângela Rozane Leal de; Trajano, Brenda Borba; Behr, Ariel (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study aims to analyze the configuration of the social network of co-authorship of Brazilian stricto sensu Postgraduate Programs in Accounting, in the 2013-2016 quadrennium, based on the production of papers published in journals of their permanent teachers. A documentary study was performed using sociometric tools to analyze 21 programs and 291 curricula, with master's and doctorate. The main results of the research show a low density of social networks of document co-authorships. However, there is an increase in this density, when compared with previous similar studies, indicating a historical increase in co-authorship. It was found that individual characteristics of teachers influence their potential to contribute to fostering partnerships, between authors and between postgraduate programs.